Pathologic examination of the placenta and its benefits in treatment plan or follow-up of patients: a cross-sectional study - Akhavan, Setareh; Borna, Sedigheh; Abdollahi, Alireza; Shariat, Mamak; Zamani, Narges (European journal of medical research, 2022)
The placental examination provides important information about the effect of maternal abnormalities on the placenta or the cause of preterm delivery, fetal growth restriction, or fetal neurodevelopmental damage. In this study, the frequency of placental pathologies of patients in a tertiary hospital was investigated. In this longitudinal and cross-sectional study, all removed placentas after any type of pregnancy termination referred to a pathological examination, within 1 year (2019-2020). All placentas were examined macroscopically and microscopically by two pathologists. Unfortunately, because of the COVID-19 pandemic, the number of pregnant women in our hospital declined. A total of 258 placentas were examined. The type of delivery in 193 cases (79.4%) was cesarean section and 50 cases (20.6%) had a vaginal delivery. In the pathological assessment of placentas, 238 (92.2%) cases were normal and 20 cases (7.8%) were abnormal. Infarct and chorioamnionitis were the pathologies with higher frequencies (4.3% and 2.7%, respectively). Intra-uterine fetal death (p = 0.701), preeclampsia (p = 0.51) had no significant difference was seen in normal and abnormal placentas. Maternal age (p = 0.83), gestational age based on the last menstrual period (p = 0.38), and gestational age based on the first ultrasound (p = 0.78) did not show a significant relationship with any of the pathological complications categories. Pathological examination of the placenta from all live-birth deliveries is not worthwhile, and it's recommended to modify the guidelines as to when the placenta is submitted for pathological evaluation.